Correct date and authorship of taxa of Middle American freshwater crabs described by Rodríguez & Smalley (1972) (not 1969) and included in Smalley (1970) (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) - Guinot, Danièle; Hendrickx, Michel E. (Zootaxa, 2014)
One subgenus and one genus of Pseudothelphusidae described by Gilberto Rodríguez and Alfred E. Smalley from Mexico have been erroneously referred to for over 40 years as variously described in 1968 and 1969. The review of the original publication indicates that these taxa were published in a journal dated 1969 that became available for distribution only in 1972. Smalley (1970), who believed that the original manuscript had been previously published, referred to some of these new taxa (i.e., Epithelphusa, E. mixtepensis, Tehuana and T. veracruzana) and provided sufficient information to make these names available in 1970, thus becoming the correct authorship for these four taxa. Therefore they must be referred to as “Rodríguez & Smalley in Smalley 1970”. A list of all affected taxa with the correct publication date and authorship is given. A list of publications in which the taxa authored by Rodríguez and Smalley were erroneously referred to as published in 1969 is also provided.